A Churn Resilience Technique on P2P Sensor Data Stream Delivery System Using Distributed Hashing - Kawakami, Tomoya; Ishi, Yoshimasa; Yoshihisa, Tomoki; Teranishi, Yuuichi (Informatica, 2015)
Recently, sensor data stream delivery system that collects sensor data periodically and delivers successively has been attracting great attention. As for this sensor data stream delivery, receivers are possible to require the same sensor data stream with different delivery cycles. Our research team proposed methods to distribute communication loads by relay nodes in the case of delivering the sensor data streams that have different data delivery cycles. However, in the previous methods, since the specic node builds delivery paths and noties related nodes, the assigned node is required to be updated when the related nodes churn. Therefore, in this paper, we propose a churn resilience technique that enhances the robustness of delivery system. We confirmed in simulations that the proposed technique improves the reliability of the delivery system.